Hepatitis E virus: a foodborne pathogen of concern in China - Jiahui Wang; Suzie Coughlan; Fengqin Li; Gabriel Gonzalez; Séamus Fanning; Nan Li; Yinping Dong; Tao Jiang (One Health Advances)
Abstract Hepatitis E, caused by hepatitis E virus (HEV), is a major global health concern with an estimated 20 million infections and 3.3 million symptomatic cases annually, resulting in approximately 44,000 deaths. It is endemic in developing countries and is emerging in developed countries. Four HEV genotypes (HEV 1 to 4) are associated with disease in humans. HEV 1 and 2 are primarily transmitted through contaminated water, whereas HEV 3 and 4 are zoonotic and transmitted predominantly through the consumption of contaminated food. The epidemiology and genotypic distribution of hepatitis E in China have changed significantly, with approximately 28,000 cases reported annually. HEV 4, instead of HEV 1 and 2, has become the most prevalent genotype. The prevalence of HEV 4 in some pig herds, as measured by the presence of HEV RNA in feces, was up to 90%. Moreover, 6% of pig liver and 11% of pig intestine intended for human consumption were positive for HEV. HEV 4 is also found in sheep, cattle, horses, rabbits, and camels. HEV-contaminated food, particularly pork products, may therefore play a major role in the transmission of HEV from animals to humans. Improving HEV surveillance at national, provincial, and local levels is crucial for reducing the infection and incidence of hepatitis E in China. Here, we reviewed the epidemiological characteristics of HEV 3 and 4, the food categories with high-risk of HEV contamination, and the impact of consuming HEV-contaminated food on human health in China.